Mechanisms underlying differential helium enrichment in shale gas of varying structural styles in the southeastern Sichuan Basin - Zhiyuan XIN; Jianfa CHEN; Jie WANG; Yong MA (Meitian dizhi yu kantan)
ObjectiveShale gas reservoirs hold considerable helium reserves despite relatively low helium abundance, establishing them as a critical replacement for helium production growth. The southeastern Sichuan Basin exhibits diverse structural styles with varying preservation conditions, leading to an unclear understanding of the distribution characteristics and enrichment patterns of helium in shale gas. Determining the mechanisms behind the differential helium enrichment in shale gas is significant for the effective utilization of helium in shale gas.MethodsFocusing on the typical shale gas reservoirs of different structural styles in the southeastern Sichuan Basin, this study explored the mechanisms underlying differential helium accumulation in shale gas in different structural styles and determined the potential play fairways for the exploration of helium in shale gas. Results and ConclusionsThe Wulong residual syncline, Baima fault-fold deformation zone, and the shallowly buried Dingshan faulted anticline, featuring unfavorable structural preservation conditions and normal formation pressure, have relatively high helium abundance, averaging 524×10−6, 606×10−6, and 534×10−6, respectively and reaching the industrial helium extraction standards. In contrast, the Jiaoshiba broad gentle anticline, Baima syncline, and deeply buried Dingshan faulted anticline, with favorable structural preservation conditions and formation overpressure, show relatively low helium abundance, averaging 335×10−6, 381×10−6, and 250×10−6, respectively. The shale gas in the Wufeng-Longmaxi formations of different structural styles in the southeastern Sichuan Basin primarily holds crust-derived helium, exhibiting great helium-generating potential. However, shales of different structural styles show nonsignificantly different helium-generating potential. The calculations of helium production based on the uranium and thorium decay theories, as well as the helium and argon isotope analyses, demonstrate that the helium in shale gas reservoirs in the southeastern Sichuan Basin is primarily of an endogenous origin, suggesting self-sourced helium reservoirs. The differences in shale gas dilution intensity, caused by the differential preservation conditions of different structural styles and resulting differential dissipation behavior of the shale gas-helium system, serve as a key factor in helium accumulation of varying structural styles in the southeastern Sichuan Basin. Additionally, the synergistic effects of the diffusion and enrichment effects of helium in micro/nano pores and the physical clogging of migration pathways with methane molecules are identified as another significant factor governing helium enrichment in shale gas. Based on the investigation of the mechanisms behind helium enrichment in shale gas of different structural styles in the southeastern Sichuan Basin, it is predicted that secondary low-pressure zones with low shale gas grades outside the basin—such as the Qijiang, Wulong, Baima, and Pengshui blocks—are potential play fairways for helium enrichment in shale gas. This study is expected to open up an entirely new direction for the exploration and production of helium in shale gas.